INDIVIDUALIZED APPROACH TO THE SURGICAL TREATMENT OF ENDOMETRIOSIS DEPENDING ON THE CLINICAL PHENOTYPE (International Conference on Medical Science, Medicine and Public Health, 2025)
This article examines the importance of an individualized approach to the surgical treatment of endometriosis based on its clinical phenotype. The variability in localization, severity, and morphological characteristics of endometriotic lesions requires personalized surgical tactics aimed at improving treatment outcomes and reducing the risk of recurrence. The study emphasizes the significance of preoperative assessment, accurate diagnosis, and multidisciplinary management to optimize surgical intervention and ensure reproductive function preservation in women with different forms of endometriosis.